PENGARUH KEPUASAN KERJA TERHADAP KINERJA PEGAWAI KANTOR KELURAHAN SEKABUPATEN BATANG HARI - Kasiyati Yunita Wulansari; Niki Kosasi (Universitas Batanghari Jambi, 2018)
This study raised concerns about the effect of job satisfaction to performance. The research was conducted within the scope of the precisely on the entire village in Batang Hari Regency. The performance of employees is among the key issues are constantly faced by the organization management. Therefore, among the tasks of the manager is a very important move employees to contribute to the success of the organization. The purpose of this study is to examine and determine the influence of job satisfaction and performance. Influence of job satisfaction and employee performance tested directly. To examine issues directly above the survey conducted by distributing questionnaires to employees village office. The results of the questionnaire were analyzed qualitatively and verification. Data analysis tool made by using Path Analysis. The results of this study indicate that the job satisfaction have an impact on performance 21,72%.